The Effectiveness of Health Promotion and Self-Management Support Program on Self-Management Behavior and Clinical Outcomes among Uncontrolled Type 2 Diabetes and Hypertension Patients - ศรเกษตริน , อติญาณ์; ทองเพชร, จินตนา; ดวงจันทร์, จุไรรัตน์ (Journal of Health Science of Thailand, 2023)
The purpose of this quasi-experimental research with two-group pretest-posttest design was to examine the effectiveness of health promotion and self-management support program on self-management behavior and clinical outcomes among uncontrolled type 2 Diabetes and hypertension patients. The samples consisted of 82 patients with type 2 diabetes mellitus and hypertension; and divided into experimental and comparison groups, 41 persons each. Research instruments included a 12-week intervention program. Data were analyzed using descriptive statistics and t-test. The results revealed that after enrolling in the program, the mean scores of hemoglobin A1C, systolic blood pressure of the experimental group were lower those of before enrolling in the program, and lower than the comparison group (p<0.05). Self-management behavior scores of the experimental group were higher than those before enrolling the program, and higher than the comparison group (p<0.05). There was no significant different between the diastolic blood pressure between the 2 groups. The researchers recommended to implement a health promotion and self-management support program among the diabetes mellitus and hypertension patients in order to improve the health outcomes.